Active learning strategies in Nursing: Cooperative and problem-based learning - Roldão Caetano, Ana-Bela Jesus (2017)
Specific strategies for active learning - cooperative learning and problem solving - wereapplied to 20 students of the third year on the Nursing Degree, in the module Maternal HealthNursing and Obstetrics. Problem-based learning follows 4 steps: problem definition; presentationof alternatives; selection of possibilities; and implementation of solutions. In this context, weformulated two problem situations where students needed to find alternatives, select the mostappropriate, discuss until reaching consensus. Cooperative learning is based on five pillars,which were followed to solve the problems: positive interdependence; individual responsibility;classroom interaction; appropriate use of interpersonal/social skills; and self-assessment. Studentswere organized in groups of three, and a role to each student was assigned, following the‘rules’ of cooperative learning. Both strategies have been used to prove the effectiveness inthe involvement and contribution to the common success as a group. At the end of the session,a questionnaire was applied. Students were asked to identify strengths and weaknesses ofthe use of pedagogical strategies already mentioned. 55% of students reported cooperativelearning as extremely important for their learning and 45% considered it very important. As forproblem solving, 35% reported it as extremely important, while 65% considered it very important.As strengths, students highlighted the promotion of critical thinking and reflection. Finally, asthe weakest point, lack of time was identified for the use of these strategies.